Sasvim lično = Totally personal - Begović, Nedžad (SaGA Production, 2005)
Totally Personal creates a historical document both droll and touching out of Begovic and his family's memories, meditations, and observations. The history begins in the communist era, continues through the war that ravaged the former Yougoslavia and into today's post-war period. --